Divine Development: The Impact of Religion on Madagascar’s Growth - ANDRIANADY, R. Josué (Theoretical and Practical Research in Economic Fields; Vol 14 No 1 (2023): TPREF, Volume XIV, Issue 1(27), Summer 2023, 2023)
This paper examines the role of religion and the church in Madagascar’s history of conflict and argues that their role has been largely overlooked in efforts to find solutions. With a significant portion of the population being animist, Christian, or Muslim, churches hold considerable influence in the country through various means, including media, education, and social support for vulnerable members of society. The paper explores whether religion plays a role in the country’s current crises and assesses its quantitative contribution to Madagascar’s economic growth and development.